Dating relationship violence in university nursing students - Cortaza Ramírez, Leticia; Torres Lagunas, María de los Ángeles; Vega Morales, Elsy Guadalupe; André Matos, Marcos; Hermida Flores, Alejandra (Horizonte Sanitario, 2023)
Objective: To identify the perception of violence in dating relationships in nursing students of a public university in Minatitlán, Veracruz, Mexico.Methodology: Descriptive, cross-sectional and correlational study, the sample consisted of 182 nursing students enrolled in a public university in Minatitlán, Veracruz, Mexico. The sampling was simple random. The Violence in Young Partner Relationships Questionnaire (VIREPA) was used, composed of 20 items with a Likert-type scale with 5 response options and sociodemographic questions.Results: 26.9% of the students indicated abuse in their past relationships and 3.8% indicated abuse in their current relationship. Differences between males and females were found in emotional abuse (z=-2.248, p=.004) and social and economic control (z=-2.681, p=.002) with higher data in males. Participant's age and partner's age was related to emotional, physical and psychological mistreatment and personal devaluation (p